Corpo/movimento na dinâmica curricular no cotidiano da educação infantil - Elesbão, Heloisa (2021)
The present study, which was developed with the Physical Education Graduate Program of the Sport and Physical Education Center at the Federal University of Santa Maria, originated from the following research question “What is the place of body/movement in the curricular dynamics in the everyday of child education?”. The main objective was to understand the place of the body/movement in the daily routine of child education of municipal schools in a municipality in the central region of Rio Grande do Sul, based on the narratives of teachers. The authors also sought to identify and analyze how teachers manifest themselves in relation to the body/movement in the curricular dynamics in the everyday of child education; to learn and analyze the documents/records regarding the pedagogical project of child education of the studied schools, in view of the Brazilian National Common Curriculum Base and the Rio Grande do Sul Curriculum Reference; to identify and analyze the knowledge of teachers about the Pedagogical Political Project of each school in relation to child education and the coordination with their teaching work within the classes, as expressed by them. In this sense, a qualitative study was carried out, with the development of narrative research. Ten members of the pedagogical team (child education teachers, principals, vice-principal and supervisor) participated in the study, with one teacher from the Margarida Solitária School and nine from the Recanto das Flores School agreeing to participate in the research. The narratives were produced in formative meetings and in semi-structured interviews conducted with the participants, individually. An initial questionnaire was also applied, in order to know, in advance, the study participants, in addition to the adoption of a field diary for recording information throughout the research. It is noteworthy that the present study was approved by the Ethics Committee of the university, being registered under the Certificate of Presentation for Ethical Appreciation 16345619.6.0000.5346 and approved by Opinion 3.470.458. Inspired by Bakhtin’s main ideas, three categories were elaborated in the analysis of the narratives: a) Seeking to understand the daily life of the school through collaborative work: a game of forces; b) Body and formative experiences about playing in childhood: senses and meanings attributed by teachers; c) Body and movement in the curricular dynamics in the everyday of childhood education: what the teachers tell. In the analysis of the narratives, it was possible to understand that the experiences lived by the teachers, in their education, did not allude to a favorable space to play. This is because their richest experiences regarding body/movement were narrated from memories lived, mainly, in the space/time of home, and, mostly, in the midst of nature, in forms of organization in which children assumed the leading role, away from the attentive look of an adult. In this sense, the teachers experienced an education and a childhood different from the one in which they are currently developing their work, thus generating a certain internal conflict. Throughout the analysis of the narratives, routine was one of the elements that gained strength, overlapping the everyday lived by children in the space/time of child education. It was also observed that the body/movement appeared only in utterances that provoked reflection or inquiry about this binomial. Thus, it is understood that the place of this binomial, in the everyday of child education of municipal schools in a municipality in the central region of Rio Grande do Sul, is peripheral, appearing mainly in aspects related to the prescription of activities, to “coming to be” and to aspects of psychomotricity, motor development or expressed through a duality between body and mind.